EXTRACURRICULAR PROGRAM FOR STUDENT SPEAKING IMPROVEMENT (NOBEL: Journal of Literature and Language Teaching, 2014)
This qualitative study explores the role of English Students Club as an extracurricular program to improve the English speaking skill of the students of the English Education Department in the Faculty of Tarbiyah (Islamic Education) State Institute for Islamic Studies (IAIN) Sunan Ampel Surabaya. The informants were 21 students of the English Education Department who were joining the club as its members. They were to fill out the questionnaires made by the writer. In further, an interview was conducted for finding more details on the club. The findings suggest three areas of concerns: 1) the students of English Department are suggested to join English Students Club as an alternative to improve their English speaking skill; 2) the programs in the club were related to speaking improvement; 3) Suggestions made by the writer in order to improve the organization management.